Total or combined application of criminal rules? For the purpose of a plenary (dis) agreement - Figueroa Navarro, Aldo Martín (2008)
The Supreme Court, by means of a Plenary Agreement for majority, it has consecrated the principle of combination of criminal statutes. Formally, the adopted decision does not have normative effectiveness because it does not reflect a sufficiently motivated and explanatory unanimous position of its content; being its practical scope very restricted. Materially,  the established principle does not respond to the national legislative tradition; it is not accepted in the comparative legislation; it contradicts the normal use of the language; and it is not adapted to a systematic, logical, progressive and appropriate interpretation of the Constitution, since it allows the judge to create a third law that harms the principle of separation of powers; it violates the principle of legality; it generates juridical insecurity and is not comfortable to the ends of prevention of the sanction.